2014
DOI: 10.1007/s00268-014-2827-1
|View full text |Cite
|
Sign up to set email alerts
|

Application of Failure Mode and Effect Analysis in Laparoscopic Colon Surgery Training

Abstract: Aim To evaluate if application of failure mode and effect analysis (FMEA) to laparoscopy training can help surgeons acquire laparoscopy skills.MethodsAfter preparing a FMEA matrix of laparoscopic sigmoidectomy, we have introduced it during three laparoscopy courses. Forty-eight surgeons, divided into 24 teams of two surgeons, have participated in three courses. During each course, every team has performed three laparoscopic sigmoidectomies in three experimental animals (1 OR session every day). Risk priority n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…However, when examined closely, there is significant variation in the scoring, and therefore, prioritisation of failures 10 18 26 27 29–32. To our knowledge, there has been no prior comparison of any simplified scoring method with the traditional method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when examined closely, there is significant variation in the scoring, and therefore, prioritisation of failures 10 18 26 27 29–32. To our knowledge, there has been no prior comparison of any simplified scoring method with the traditional method.…”
Section: Discussionmentioning
confidence: 99%
“…The top 20% of failures by CI were designated ‘critical’ based on the Pareto Principle (80/20 rule) 25. An RPN of 300 was chosen as a threshold above which failure modes would be designated ‘critical’ based on prior literature and research team consensus 26 27…”
Section: Methodsmentioning
confidence: 99%
“…In a surgical setting, HFMEA has been used to improve patient safety in laparoscopy and ophthalmic surgery . HFMEA has also been used to reduce medication error harm events in paediatric anaesthesia .…”
Section: Introductionmentioning
confidence: 99%
“…Also in a recent study by our group we have shown that concentrating on evitable errors during colorectal laparoscopy training in pigs can yield better results than traditional training which focus on technical aspects of laparoscopy. With our approach we were able to obtain interesting results even with low number of repetition, which translates into fewer experimental animals that need to be operated in order to train one trainee (1).…”
mentioning
confidence: 99%
“…The rise of minimally invasive procedures has increased the interest of many surgeons in laparo-and endoscopy training models that use live animal. As a result, pigs have been frequently used as a model for colorectal laparoscopic surgery (1), sheep as a gynecologic and transvaginal NOTES model (2) and rabbit as a pediatric thoracoscopy model (3). Indeed, the introduction of a new technique based on animal experiment can lead to steeper learning curve (1) and finally to less complications in humans after clinical application of the technique (4).…”
mentioning
confidence: 99%